THE CONTROVERSY OVER MINISTRY DISSOLUTION: INSIGHTS INTO INDONESIA’S PRESIDENTIAL SYSTEM - Mutawalli, Muhammad; Zainal Amin Ayub; Amah, Emmanuel Ibiam (Faculty of Law, Universitas Pasundan, 2023)
This study examines the strengthening of presidential authority and investigates the polemics surrounding the dissolution of ministries in Indonesia, with a focus on the provisions of Law Number 39 of 2008. Employing a normative qualitative approach, the research draws on data collected through documentation, literature reviews, and interviews with officials, ministry representatives, and state studies activists in South Sulawesi and West Sulawesi. The findings highlight the critical importance of constructive collaboration and communication between the president, as the head of the executive, and parliament, as the legislature, to achieve consensus on cabinet formation. Effective dialogue fosters the creation of a cabinet composition that ensures both functionality and sufficient political support. However, the research identifies significant challenges, including a lack of transparency and limited public participation in legislative processes, as well as insufficient inter-agency collaboration in the drafting and enactment of laws. The study’s novelty lies in its exploration of the interplay between executive authority and legislative oversight in cabinet formation within Indonesia’s presidential system. By shedding light on the implications of these dynamics, the research contributes to the discourse on governance reform and emphasizes the need for enhanced institutional synergy to promote accountability and public trust.